PERMINTAAN PERSAKSIAN DAN PEMBEBASAN HUTANG MAYIT DALAM TRADISI UPACARA PEMBERANGKATAN JENAZAH(Studi Living Hadith) - -, Khamim (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2016)
A phenomenon living hadith in community Nahliyyin in Jombang is a tradition of asking testimony and guaranteed the deceased debt conducted after jenazah prayer. This article investigates that community tradition in Jombang by using phenomenology approach, and normative-textual approach to examine the truth of that tradition if it is measured by using hadith text. In conclusion, the tradition of asking testimony for deceased after conducted jenazah prayer in fact is appropriate with the Prophet’s doctrine, because that tradition is conducted to pray deceased, and the purpose of jenazah prayer is asking help. Furthermore, the tradition of asking the deceased debt free after conducting jenazah prayer is still in line with hadith of Salmat ibn al-Akwa’ about the rejection of the Prophet conducted prayer for deceased before there is a person who guarantees his/her debt, because after fathu makkah is happened the Prophet is the first person who guarantees the debt of died Mukmin. That tradition is considered still in line with the meaning of hadith, so that this living hadith is considered true and appropriate with Islam syari’at.Keywords; asking testimony, debt free, Living Hadith